Platelets and Infections – Complex Interactions with Bacteria - Hamzeh-Cognasse, Hind; Damien, Pauline; Chabert, Adrien; Pozzetto, Bruno; Cognasse, Fabrice; Garraud, Olivier (Frontiers in Immunology, 2015)
Platelets can be considered sentinels of vascular system due to their high number in the circulation and to the range of functional immunoreceptors they express. Platelets express a wide range of potential bacterial receptors, including complement receptors, FcγRII, Toll-Like Receptors but also integrins conventionally described in the hemostatic response, such as GPIIb-IIIa or GPIb. Bacteria bind these receptors either directly, or indirectly via fibrinogen, fibronectin, the first complement C1q, the von Willebrand Factor, etc. The fate of platelet bound bacteria is questioned. Several studies reported the ability of activated platelets to internalize bacteria such as Staphylococcus aureus or Porphyromonas gingivalis, though there is no clue on what happens thereafter. Are they sheltered from the immune system in the cytoplasm of platelets or are they lysed? Indeed, while the presence of phagolysosome has not been demonstrated in platelets, they contain antimicrobial peptides that were shown to be efficient on S. aureus. Besides, the fact that bacteria can bind to platelets via receptors involved in hemostasis suggests that they may induce aggregation; this has indeed been described for Streptococcus sanguinis, S. epidermidis or C. pneumoniae. On the other hand, platelets are able to display an inflammatory response to an infectious triggering. We, and others, have shown that platelet release soluble immunomodulatory factors upon stimulation by bacterial components. Moreover, interactions between bacteria and platelets are not limited to only these two partners. Indeed, platelets are also essential for the formation of Neutrophil Extracellular Traps by neutrophils, resulting in bacterial clearance by trapping bacteria and concentrating antibacterial factors but in enhancing thrombosis. In conclusion, the platelet-bacteria interplay is a complex game; its fine analysis is complicated by the fact that the inflammatory component adds to the aggregation response.